Aptamer Blocking Strategy Inhibits SARS‐CoV‐2 Virus Infection. Issue 18 (10th March 2021) - Sun, Miao; Liu, Siwen; Wei, Xinyu; Wan, Shuang; Huang, Mengjiao; Song, Ting; Lu, Yao; Weng, Xiaonan; Lin, Zhu; Chen, Honglin; Song, Yanling; Yang, Chaoyong
Abstract: The COVID‐19 pandemic caused by SARS‐CoV‐2 is threating global health. Inhibiting interaction of the receptor‐binding domain of SARS‐CoV‐2 S protein (SRBD ) and human ACE2 receptor is a promising treatment strategy. However, SARS‐CoV‐2 neutralizing antibodies are compromised by their risk of antibody‐dependent enhancement (ADE) and unfavorably large size for intranasal delivery. To avoid these limitations, we demonstrated an aptamer blocking strategy by engineering aptamers' binding to the region on SRBD that directly mediates ACE2 receptor engagement, leading to block SARS‐CoV‐2 infection. With aptamer selection against SRBD and molecular docking, aptamer CoV2‐6 was identified and applied to prevent, compete with, and substitute ACE2 from binding to SRBD . CoV2‐6 was further shortened and engineered as a circular bivalent aptamer CoV2‐6C3 (cb‐CoV2‐6C3) to improve the stability, affinity, and inhibition efficacy. cb‐CoV2‐6C3 is stable in serum for more than 12 h and can be stored at room temperature for more than 14 days. Furthermore, cb‐CoV2‐6C3 binds to SRBD with high affinity ( K d =0.13 nM) and blocks authentic SARS‐CoV‐2 virus with an IC50 of 0.42 nM. Abstract : We propose an aptamer blocking strategy to inhibit SARS‐CoV‐2 infection. With the advantages of small size, rapid kinetics, high stability, sophisticated programmability and high security, our aptamers have great potential as prophylactic and therapeutic agents, which could greatly assist in the intervention of prevailing and emerging infectious diseases other than COVID‐19.